Examination of photocatalytic redox process in removal of bisphenol-A in wastewater - Liu, Jaime LiShan. (2009)
Advanced oxidation processes (AOP) is an aqueous phase oxidation system, widely known for organic contaminants degradation. In this project, AOP is applied through heterogeneous photocatalysis under irradiation of UV and visible light. The focus of this project is to synthesize an active TiO2 photocatalyst that is visible light responsive and evaluate its performance with reference to commercial Degussa P25. Nitrogen doped TiO2 at calcined temperature of 400oC and 600oC has been produced for the study. Characterizations of the synthesized sample were done to understand its morphology, composition, specific surface area, and photo-absorption property. Photocatalytic oxidations of bis-phenol A were carried out using synthesized N-TiO2 and P25. The experimental analysis reflected the ability of photocatalyst to perform photocatalytic oxidation under UVA condition and visible light irradiation with degradation of 55.6 % and 30.8% for 400oC N-TiO2 and 59.5% and 25.2% for 600oC N-TiO2 respectively. It is evident from the findings that nitrogen doping would be dependent the annealing temperature of photocatalyst, photocatalyst loading and presence of dissolved oxygen to achieve a certain photodegradation rate and efficiency. However due to the unavailability of resources and time constraint, experiment was conducted once for each operational parameters.